Analisis Fungsi Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dalam Kasus Pernikahan Beda Agama - Ninda Ma'rifatul Hasni; Margo Hadi Putra (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study discusses the analysis of the function of the Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage for interfaith marriages. The purpose of this study is to discuss and examine the analysis of Law Number 1 of 1974 concerning Marriage for interfaith marriages based on their legal functions, which include philosophical, juridical and sociological. The study used a qualitative descriptive method with data collection techniques carried out through interviews, documentation and observation. The results of this study indicate that Law Number 1 of 1974 concerning Marriage makes it very difficult for interfaith couples to obtain the legality of marriage